Peran Keluarga dan Kualitas Hidup Pasien Kanker Serviks - Tiyas Kusumaningrum; Retnayu Pradanie; Esti Yunitasari; Sih Kinanti (Jurnal Ners, 2016)
Introduction. Cervical cancer diagnosis has been a major burden both for patients and their family. For patients, cervical cancer obliterated some of their role as a wife and a mother. Most patients with advance cancer have low score of quality of life indicating they have problems. Family must take care of their beloved ones dealing with the diagnosis, treatment, and side effects of cervical cancer. Family as a caregiver might be ill prepared to undertake that role. The objective of this research was to identify the correlation of family health task on quality of life in patients with cervical cancer.Methods. This research employed cross-sectional design. Population in this research was all patients with cervical cancer in gynecology ward Dr Soetomo Hospital in Surabaya. Participant for this research were patients with cervical cancer and their family. Data were taken by structured interview using Fact Cx for Quality of life and family health task question form. Linear regression analysis was applied with level of significance ≤0.05.Results. Most family had moderate level of family health task while most patients also have moderate level of quality of life. Unfortunately there are no significance correlations of family health task on quality of life in patients with cervical cancer.Discussion. Quality of life in patient with cervical cancer was not affected directly by their family health task. Nonetheless patient gratefully thanks family for their support during their cancer treatments.